Asymmetric Synthesis of 3‐Pyrrolines through an Aryne‐Induced Domino Process. Issue 4 (9th February 2021) - Hwu, Jih Ru; Panja, Avijit; Gupta, Nitesh K.; Huang, Wen‐Chieh; Hu, Yu‐Chen; Lin, Chun‐Cheng; Hwang, Kuo‐Chu; Chan, Wei‐Jen; Tsay, Shwu‐Chen
Abstract: Production of chiral compounds by green processes like domino reactions is of importance to environmental protection and sustainable development. Nevertheless, finding an appropriate catalyst to control enantioselectivity with satisfaction is a major challenge. Here, we report the accomplishment of a newly developed domino reaction for synthesizing optically active 3‐pyrrolines, a class of compounds with various biological properties. The reaction involves the use of (trimethylsilyl)aryl triflates, Schiff bases, and alkynes in the presence of a chiral catalyst ( R )‐(−)‐1, 1′‐binaphthyl‐2, 2′‐diyl hydrogenphosphate. The key features of this new reaction include the generation of a single product in very good yields (75–85%) with high stereo‐ and enantio‐selectivity; the enantiomeric ratio reaches as high as 98.5 : 1.5. Moreover, it involves an aryne‐induced domino reaction and an unusual 1, 4‐intramolecular proton transfer, which overwhelms the well‐established 1, 5‐proton transfer. Abstract : A novel "single‐flask" reaction was developed for efficient synthesis of optically active cis ‐3‐pyrrolines from arynes, Schiff bases, alkynes, and ( R )‐(−)‐BNPPA.